Impact of replacing sow milk with milk replacer on growth performance, intestinal development, bacterial profile and muscular maturation in neonatal and nursery piglets - Zhang, Yuwei; Liu, Shiya; Zhou, Qiang; Liu, Yang; Hu, Liang; Zhang, Ruinan; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Wu, De; et al. (Frontiers in Veterinary Science, 2025)
Along with the increasing litter sizes in pig industry, using milk replacer (MR) as a nutrient supplement has been widely practiced, yet the effects of replacing sow milk (SM) with MR on growth and development of piglets remain unclear. This study evaluated the differential effects of MR versus SM on growth performance, body composition, muscle fiber types, and intestinal health of piglets during the neonatal and nursery periods. Forty 2-day-old piglets, selected from 10 healthy sows, were randomly divided into two groups receiving either SM or MR ad libitum until postnatal day 23 (PND 23), then transitioned to be fed with nursery diet until PND 37. Blood, muscle, and intestinal tissues, along with colonic digesta and carcass samples, were collected on PND 12 (n = 10) and PND 37 (n = 10) for analysis of parameters related to intestinal function, microbiota composition and muscular development. The results showed that MR-fed piglets had lower average daily gain (ADG) and higher diarrhea index during the neonatal period. During the nursery period, however, MR-fed piglets had significantly higher average daily feed intake (ADFI) and ADG. Compared to SM-fed piglets, MR-fed piglets had a lower percentage of fast twitch fibers, but a higher percentage of slow twitch fibers on PND 12, along with lower body fat content on both PND 12 and PND 37. In addition, MR-fed piglets had significantly deeper crypt depth, increased mRNA expressions of inflammatory genes, and lower alpha diversity on PND 12. On PND 37, however, MR-fed piglets had higher villus height, increased sucrase activity and alpha diversity. On PND 12, likewise, MR-fed piglets were enriched with Prevotella associated with diarrhea, while SM-fed piglets were enriched with Lachnospiraceae associated with body fat deposition. In contrast, on PND 37, MR-fed piglets were enriched with commonly recognized beneficial bacteria, such as f_Muribaculaceae, g_Prevotellaceae_NK3B31_group, f_Oscillospiraceae and f_Rikenellaceae. These findings indicate that piglets fed MR experienced temporary growth check and intestinal complications in neonatal period, but intriguingly MR piglets had higher feed intake, compensatory growth, and recovery of intestinal function during the nursery period.